Eye movement desensitization and reprocessing im psychokardiologischen Setting: Traumaspezifische Verarbeitung des Schocks durch den implantierbaren Kardioverter-Defibrillator = Eye movement desensitization and reprocessing in psychocardiological settings : trauma-specific processing of shock due to implantable cardioverter-defibrillators - Peregrinova, Ludmila; Hamann-Weber, Bettina (Psychotherapeut, 2017)
According to the guidelines of cardiological societies, patients should be screened for trauma symptoms in addition to depression and anxiety after receiving implantable cardioverter defibrillator (ICD) shocks. This has resulted in an increasing number of patients seeking psychocardiological help. The effective processing of acute cardiac events, which are experienced as traumatic, represents an important prerequisite for further coping with the underlying chronic cardiac disease. However, trauma-specific treatment strategies after ICD shocks are rarely published. The aim of this article is to present the trauma-specific technique of eye movement desensitization and reprocessing (EMDR) in patients after ICD shocks. The clinical experiences confirm the safety and acceptance of this method by the patients. Further randomized controlled studies are needed to confirm the initial indications for its effectiveness.
Gesehen am 15.11.2018